2006
DOI: 10.1529/biophysj.106.082776
|View full text |Cite
|
Sign up to set email alerts
|

Curvature and Hydrophobic Forces Drive Oligomerization and Modulate Activity of Rhodopsin in Membranes

Abstract: G protein-coupled receptors (GPCRs) are essential components of cellular signaling pathways. They are the targets of many current pharmaceuticals and are postulated to dimerize or oligomerize in cellular membranes in conjunction with their functional mechanisms. We demonstrate using fluorescence resonance energy transfer how association of rhodopsin occurs by long-range lipid-protein interactions due to geometrical forces, yielding greater receptor crowding. Constitutive association of rhodopsin is promoted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
327
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 272 publications
(348 citation statements)
references
References 99 publications
(244 reference statements)
18
327
3
Order By: Relevance
“…A few experimental studies addressed the relation between membrane thickness and oligomerization. Using FRET experiments, it was shown that the reduction of membrane thickness or the increase of the protein/lipid molar ratio promotes rhodopsin association (Brown, 1994;Botelho et al, 2006).…”
Section: Influence Of the Lipid Environmentmentioning
confidence: 99%
“…A few experimental studies addressed the relation between membrane thickness and oligomerization. Using FRET experiments, it was shown that the reduction of membrane thickness or the increase of the protein/lipid molar ratio promotes rhodopsin association (Brown, 1994;Botelho et al, 2006).…”
Section: Influence Of the Lipid Environmentmentioning
confidence: 99%
“…Light-induced retinal isomerization destabilizes the inactive receptor conformation (17,18). Activation entails large-scale movements of helices H5 and H6 together with H7 (19,23), exposing transducin (G t ) recognition sites on the C2 and C3 cytoplasmic loops (22). A current picture (17,27,44) is that photon absorption leads to the major reactions (17,44):…”
Section: Changes In Local Retinal Structure and Dynamics Initiate Colmentioning
confidence: 99%
“…Such changes in local retinal dynamics (Fig. 3) underlie the influences of retinylidene methyl groups on the Meta I-Meta II equilibrium (34) within the pressure field of the lipid bilayer (22). In the currency of protein dynamics, large-scale functional motions involve displacements of many atoms within the protein.…”
Section: Collective Protein Fluctuations Within the Membrane Lipid Bimentioning
confidence: 99%
See 2 more Smart Citations